2016
DOI: 10.1371/journal.pone.0161989
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation in Length-Weight Relationships and Condition of the Ribbonfish Trichiurus lepturus (Linnaeus, 1758): Implications for Fisheries Management

Abstract: Knowledge of length-weight relationships for commercially exploited fish is an important tool for assessing and managing of fish stocks. However, analyses of length-weight relationship fisheries data typically do not consider the inherent differences in length-weight relationships for fish caught from different habitats, seasons, or years, and this can affect the utility of these data for developing condition indices or calculating fisheries biomass. Here, we investigated length-weight relationships for ribbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
1
25
1
1
Order By: Relevance
“…Variation in the Length–weight relationship between regions (West Atlantic, n = 30; East Atlantic, n = 65; English Channel, n = 60; Baltic Sea, n = 40), was examined by regression analysis on log-transformed data ( R Development Core Team, 2013 ). We calculated relative weight (Wr) as the ratio of the observed weight divided by the predicted weight (from the regression obtained above) to obtain an index of body condition that is more appropriate for fish like lumpfish that have an unusual body shape ( Nahdi, Garcia de Leaniz & King, 2016 ). The most plausible number of age classes represented in the samples, and the mean size at age ( Macdonald & Pitcher, 1979 ) were calculated through mixture analysis of length-frequency data using PAST v3.17 ( Hammer, Harper & Ryan, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Variation in the Length–weight relationship between regions (West Atlantic, n = 30; East Atlantic, n = 65; English Channel, n = 60; Baltic Sea, n = 40), was examined by regression analysis on log-transformed data ( R Development Core Team, 2013 ). We calculated relative weight (Wr) as the ratio of the observed weight divided by the predicted weight (from the regression obtained above) to obtain an index of body condition that is more appropriate for fish like lumpfish that have an unusual body shape ( Nahdi, Garcia de Leaniz & King, 2016 ). The most plausible number of age classes represented in the samples, and the mean size at age ( Macdonald & Pitcher, 1979 ) were calculated through mixture analysis of length-frequency data using PAST v3.17 ( Hammer, Harper & Ryan, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Variation in the length-weight relationship between regions (West Atlantic, n = 30; East Atlantic, n = 65; English Channel, n = 60; Baltic Sea, n = 40), was examined by regression analysis on log-transformed data. We calculated relative weight (Wr) as the ratio of the observed weight divided by the predicted weight (from the regression obtained above) to obtain an index of body condition that is more appropriate for fish like lumpfish that have an unusual body shape (Nahdi et al, 2016). The most plausible number of age classes represented in the samples, and the mean size at age (Macdonald & Pitcher, 1979) were calculated through mixture analysis of length-frequency data using PAST v3.17 (Hammer et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In Malaysia, the value is higher at 3.190 (Ahmad et al 2003), while in Australia (Willing and Pender 1989) showed that the value of b is 2.965. The different could probably due to variability in each local environment and ecosystem and human pressures on marine biodiversity (Nahdi et al 2016).…”
Section: Length-weight Relationshipmentioning
confidence: 99%